Students’ perceptions of teaching methods used at South African higher education institutions - Govender, Samantha (South African Journal of Higher Education, 2016)
The purpose of this study was to ascertain student perceptions of selected methods used for teaching undergraduate students. A total of 200 level 3 undergraduates in the Faculty of Education from a university in KwaZulu-Natal completed a questionnaire about the frequency of various teaching methods used by lecturers, their perceptions of the most effective ones and reasons for their preferences. The findings reveal that the lecture method was the one most often used. Students felt that they were less frequently exposed to alternative teaching methods that require them to participate actively. Although lectures are useful when teaching large groups and enable lecturers to present factual material logically, the communication is one-way and students often feel passive. Two important recommendations that emerge from the study are for lecturers to expose students to multiple teaching methods thereby maintaining a balance, and to consider using innovative educational technology to enhance the quality of teaching and learning.